Giving girls a voice communication strateg y for girls' education. - UNICEF. Eastern and Southern Africa Regional Office ([Nairobi] : UNICEF Eastern & Southern Africa Regional Office)
Recently, a group of young people from Eritrea, Ethiopia, Kenya, Moz ambique, Uganda, and Zambia met in Nairobi to discuss a communication s trategy for scaling up girls' education. This video highlights some of the issues discussed in the 3 day workshop.
Summary from videodisc container.
Keywords: Women in Education